National Health Service – Some Achievements (Res Medica, 2013)
The National Health Service has now been in existence for over fifteen years, and is firmly established as one of the features of Twentieth Century Britain. There are many criticisms of it and many defects and deficiencies; one has only to read the newspapers—particularly the correspondence columns — to have them pointed out. However, it is good to look at the service’s successes and achievements, not in any sense of complacency, but rather in the spirit of Sir Winston Churchill’s famous minute, written in 1942, on the possibility of establishing artificial harbours on the Invasion Beaches of Europe:— “Let me have the best solution worked out. Don’t argue the matter; the difficulties will argue for themselves.”